Somatic Spikes Regulate Dendritic Signaling in Small Neurons in the Absence of Backpropagating Action Potentials - Myoga, Michael H. (Society for Neuroscience, 2009)
Somatic spiking is known to regulate dendritic signaling and associative synaptic plasticity in many types of large neurons, but it is unclear whether somatic action potentials play similar roles in small neurons. Here we ask whether somatic action potentials can also influence dendritic signaling in an electrically compact neuron, the cerebellar stellate cell (SC). Experiments were conducted in rat brain slices using a combination of imaging and electrophysiology. We find that somatic action potentials elevate dendritic calcium levels in SCs. There was little attenuation of calcium signals with distance from the soma in SCs from postnatal day 17 (P17)–P19 rats, which had dendrites that averaged 60 μm in length, and in short SC dendrites from P30–P33 rats. Somatic action potentials evoke dendritic calcium increases that are not affected by blocking dendritic sodium channels. This indicates that dendritic signals in SCs do not rely on dendritic sodium channels, which differs from many types of large neurons, in which dendritic sodium channels and backpropagating action potentials allow somatic spikes to control dendritic calcium signaling. Despite the lack of active backpropagating action potentials, we find that trains of somatic action potentials elevate dendritic calcium sufficiently to release endocannabinoids and retrogradely suppress parallel fiber to SC synapses in P17–P19 rats. Prolonged SC firing at physiologically realistic frequencies produces retrograde suppression when combined with low-level group I metabotropic glutamate receptor activation. Somatic spiking also interacts with synaptic stimulation to promote associative plasticity. These findings indicate that in small neurons the passive spread of potential within dendrites can allow somatic spiking to regulate dendritic calcium signaling and synaptic plasticity.